Flow-centric air traffic control: human in the loop simulation experiment - Ahmad Sufian Bin Jumad (2023)
Flow-Centric Operations (FCO) is a novel air traffic control concept for the management of en-route airspace in which controller assignment is determined by grouping factors such as similarity in trajectory rather than by the physical position of the flight (by area sectors). FCO therefore anticipates that two aircraft, which are controlled by two respective air traffic control officers (ATCOs), may coexist in the same volume of airspace. FCO’s requirements or enablers in terms of technical preparedness are not established. FOC might provide elasticity in capacity by creating more flows by splitting the incoming flows, as many as needed. It might be able to split the incoming traffic to achieve greater capacity, compared to the capacity level attained by splitting area sectors. In addition, it might offer the Capacityon-Demand capability; in a low traffic hour or day, an area control centre shall roster fewer ATCOs, and in a high traffic hour or day, more ATCOs. Through the conduct of Human-inthe-Loop simulation involving a total of 6 ATCOs from Civil Aviation Authority of Singapore, across a 11-day period, qualitative feedback was solicited from the ATCOs. Tokenised comments are categorised into 3 sets: safety concerns, concept design parameters, and Human-Machine Interface. Key takeaways include: the need to understand further into the difficulty level of different crossing and merging and not simply have a uniform perceived difficulty or weight for such scenarios, the importance of considering the difficulty/complexity factor rather than the volume of traffic when dealing with assignment strategy and the importance of considering human-machine interfaces dealing with zoom level or secondary windows. Based on this simulation study, we discuss possibilities for future and follow up studies. The most important appears to be creating ideal air traffic flow for ATCOs, which minimises air traffic inferences at air traffic hot-spot areas, in order to realise FCO under increasing air traffic demands. For this purpose, key ideas of our future works are managing time-varying air traffic at the hot-spots based on queue-based approaches, development of geometric algorithms for ergonomic spatially and temporally dynamic area of responsibility for ATCOs, and studies on FCO-specific human factors and ATCO-to-ATCO coordination mechanisms.